Is Information Literacy Instruction Essential to Graduate Students? - A Perspective Based on the Review of Research Literature on Graduate Students’ Information Behavior - Li, Ping (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This is a review of research literature on graduate students’ information behavior. It aims at determining emergent patterns on graduate students’ information behavior, based on which recommendations are made as to whether graduate students need information literacy instruction and, if yes, what kinds of instruction are needed. Cette communication est une revue de la littérature de recherche sur les comportements informationnels des étudiants universitaires de 2e et 3e cycle. L’objectif est d’identifier des modèles émergents du comportement informationnel de ces étudiants, en fonctions des critères de recommandation permettant de déterminer s’ils ont ou non besoin de formation en maîtrise de l’information et, si oui, le type de formation nécessaire.